Optimising load transfer using temporary supports in monolithic construction - Švolík, Milan; Makýš, Peter; Šťastný, Patrik; Ďubek, Marek (Acta Polytechnica, 2024)
When constructing a ceiling slab, it is essential that the load is effectively transferred to the lower floors. However, challenges arise when the lower ceiling slabs do not meet the specified design strengths, potentially indicating inadequate load bearing capacity. This article explores a novel approach to solving this problem by using supports that are not traditionally used for slab formwork, but rather as backpropping mechanisms. These supports serve as static reinforcements for the ceiling slabs, optimising the load distribution. This article delves into the distinctive features of these supports and evaluates their potential impact on the overall structural integrity of the implemented design.